Islamization in Pakistan from Iskandar Ali Mirza to General Zia ul Haq: Socio-political Comparative Analysis - Ahmed, Ishfaq; Fitrianto, Achmad Room; Hamid, Ahmed Munir (Nadwa: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to critically analyze the process of Islamization with the view of economic, political, and constitutional development in Pakistan. For this purpose, in-depth literature, and newspaper articles were analyzed from 1956 to 1988.  The findings of the in-depth analysis show that from 1956 to 1988, Pakistan saw strong military rule comprising 25 years of martial law collectively during this period. The first attempt to bring Islamization into the country was carried out in 1956 by promulgating an objective resolution. To successfully implement the agenda of Islamization, different government-based Islamic institutions were established: the Islamic Advisory Council and the Islamic Research Center. Bhutto and Zia came into power on the Islamic slogans; Muslim equality and Islamic system. Bhutto brought the 1973 constitution and declared Islam as a religion of the state and also declared Ahamdiya as non-Muslims due to their un-Islamic beliefs. General Zia introduced different Islamic laws through presential order, which describes the harsh punishment for major crimes, changed the direction of the law of evidence, and established Shariat Courts, which were specialized in giving the verdict according to the principles of Islam. It is evident that the political instability and intense martial law led Pakistan into a “politically devastated country” and most of the rulers during this period were strongly against democracy. Therefore, this study helps the reader to figure out the impact of the Islamization policies of different rulers on Pakistani society.